Nucleoside Analogs: A Review of Its Source and Separation Processes - Pan Wang; Tao Cheng; Jianming Pan (Molecules, 2023)
Nucleoside analogs play a crucial role in the production of high-value antitumor and antimicrobial drugs. Currently, nucleoside analogs are mainly obtained through nucleic acid degradation, chemical synthesis, and biotransformation. However, these methods face several challenges, such as low concentration of the main product, the presence of complex matrices, and the generation of numerous by-products that significantly limit the development of new drugs and their pharmacological studies. Therefore, this work aims to summarize the universal separation methods of nucleoside analogs, including crystallization, high-performance liquid chromatography (HPLC), column chromatography, solvent extraction, and adsorption. The review also explores the application of molecular imprinting techniques (MITs) in enhancing the identification of the separation process. It compares existing studies reported on adsorbents of molecularly imprinted polymers (MIPs) for the separation of nucleoside analogs. The development of new methods for selective separation and purification of nucleosides is vital to improving the efficiency and quality of nucleoside production. It enables us to obtain nucleoside products that are essential for the development of antitumor and antiviral drugs. Additionally, these methods possess immense potential in the prevention and control of serious diseases, offering significant economic, social, and scientific benefits to the fields of environment, biomedical research, and clinical therapeutics.